Beliefs about knowledge sebagai pemediasi antara pengaruh personality factor terhadap academic performance - Alfiati Silfi (SYNERGY: Jurnal Bisnis dan Manajemen, 2021)
The objective of the study is to investigate the influence between personality factors towards Academic performance with Beliefs about knowledge as Mediated. Personality factors consist of five dimensions of personality known as The Big Five Personality. Then, the academic Performance uses Grade Point Average (GPA). The sample in this study is from 250 accounting students at several uiversities in Indonesia. Data were analyzed with SPSS by regression analysis to examine the influence of Personality factors towards Academic Performance. The result shows that all hypotheses are eaccepted.